Microenvironmental hCAP-18/LL-37 promotes pancreatic ductal adenocarcinoma by activating its cancer stem cell compartment. Issue 12 (3rd April 2015) - Sainz, Bruno; Alcala, Sonia; Garcia, Elena; Sanchez-Ripoll, Yolanda; Azevedo, Maria M; Cioffi, Michele; Tatari, Marianthi; Miranda-Lorenzo, Irene; Hidalgo, Manuel; Gomez-Lopez, Gonzalo; Cañamero, Marta; Erkan, Mert; et al.
Abstract : Objectives: The tumour stroma/microenvironment not only provides structural support for tumour development, but more importantly it provides cues to cancer stem cells (CSCs) that regulate their self-renewal and metastatic potential. This is certainly true for pancreatic ductal adenocarcinomas (PDAC), where tumour-associated fibroblasts, pancreatic stellate cells and immune cells create an abundant paracrine niche for CSCs via microenvironment-secreted factors. Thus understanding the role that tumour stroma cells play in PDAC development and CSC biology is of utmost importance. Design: Microarray analyses, tumour microarray immunohistochemical assays, in vitro co-culture experiments, recombinant protein treatment approaches and in vivo intervention studies were performed to understand the role that the immunomodulatory cationic antimicrobial peptide 18/LL-37 (hCAP-18/LL-37) plays in PDAC biology. Results: We found that hCAP-18/LL-37 was strongly expressed in the stroma of advanced primary and secondary PDAC tumours and is secreted by immune cells of the stroma (eg, tumour-associated macrophages) in response to tumour growth factor-β1 and particularly CSC-secreted Nodal/ActivinA. Treatment of pancreatic CSCs with recombinant LL-37 increased pluripotency-associated gene expression, self-renewal, invasion and tumourigenicity via formyl peptide receptor 2 (FPR2)- and P2X purinoceptor 7 receptor (P2X7R)-dependent mechanisms, which could be reversed by inhibiting these receptors. Importantly, in a genetically engineered mouse model of K-Ras-driven pancreatic tumourigenesis, we also showed that tumour formation was inhibited by either reconstituting these mice with bone marrow from cathelicidin-related antimicrobial peptide (ie, murine homologue of hCAP-18/LL-37) knockout mice or by pharmacologically inhibiting FPR2 and P2X7R. Conclusions: Thus, hCAP-18/LL-37 represents a previously unrecognised PDAC microenvironment factor that plays a critical role in pancreatic CSC-mediated tumourigenesis.